Soft Nano‐Imprint Lithography of Rare‐Earth‐Doped Light‐Emitting Photonic Metasurface. Issue 21 (15th August 2022) - Chehadi, Zeinab; Montanari, Michele; Granchi, Nicoletta; Modaresialam, Mehrnaz; Koudia, Mathieu; Abel, Mathieu; Putero, Magali; Grosso, David; Intonti, Francesca; Abbarchi, Marco
Abstract: Sol–gel chemistry and nano‐imprint lithography (soft‐NIL) can be combined for the fabrication of nano‐patterns with large vertical aspect ratio over large scales. The possibility to frame via soft‐NIL metal oxides materials featuring a large refractive index and low absorption coefficient, opens new avenues for light management. In spite of its importance, the integration of light emitters in these materials has been mostly investigated in flat layers, limiting their efficiency and versatility. Here it is shown that ZrO2 can be combined with light emitting Eu 3+ ions and framed via soft‐NIL to form large arrays of pillars atop a 2D residual layer. The chemical precursor solutions and the nano‐imprint technique are developed for photonic metasurfaces sustaining sharp resonances ascribed to quasi‐guided modes and lattice modes, as accounted for by finite difference time domains simulations. These resonances enable for a record extraction of the Eu 3+ forward emission up to ≈200 times with respect to the flat counterpart within a relatively small detection angle (≈ ±16° around the vertical direction). These results are relevant for light‐emitting displays, down‐ and up‐conversion processes for light detection such as scintillators for X‐ray and for light amplifiers based on rare‐earth emitters. Abstract : Sol–gel dip‐coating and nano‐imprint lithography are combined to embed luminescent Eu 3+ ions within photonic metasurfaces based on ZrO2 . The structures are composed of pillars organized in a square lattice, sitting on a 2D layer sustaining quasi‐guided modes. The coupling between the photoluminescence and the photonic resonances provides a 200‐fold enhancement of light extraction within a small solid angle.